Bio-activity guided isolation of the active constituents from Barringtonia asiatica Linn. seeds. - Gamarcha, Leandro Tacluyan
Extraction of four hundred thirty (430g) grams powered air-dried seeds of barringtonia asiatica with 70 methanol yielded a yellowish concentrate. Liquid-liquid extraction of the concentrated methanolic extract with hexane, dichloromethane and ethyl acetate as solvents yielded 53.87 of hexane extract which is the highest, dichloromethane with 0.88 and ethyl acetate with the lowest yield of 0.29. The remainder was the aqueous portion., Analgesic activity of the three extracts (hexane, dichloromethane and ethyl acetate) gave percentage reduction of 42.8, 37.34 and 47.71, respectively. All showed significant difference compared to mefenamic acid having percentage reduction of 24.60. The three extracts showed no significant difference among them. The aqueous extract gave 57.46 reduction in mice squirms. This was significantly different from all other treatments. There was no significant difference however, in the percentage reduction in mice squirms between the aqueous and the crude. TLC profile of the three extracts (hexane, dichloromethane and ethyl acetate) together with the crude using hexane-ethyl acetate (10:1) as solvents showed a common spot having Rf value of 0.06. this component is relatively polar in character and could be a diterpene based on its color reaction with 5 vanillin. This could be one of the components responsible for its analgesic activity. Vacuum liquid chromatography of the hexane extract using fifteen (15) solvent system yielded 15 solvent fractions. Fractions 1-8, fractions 9-12 and fractions 13-15 were pooled based on the similarities in their TLC profiles. Theses were labeled as fraction 1,2 and 3, respectively. the yields of these fractions were 0.15, 0.99 and 0.71, respectively. Bioactivity of fraction 2 and fraction 3 gave 14.58 and 31.49 reduction of mice squirms, showing that fraction 3 was a better analgesic. It was even more active than mefenamic acid, which gave percentage reduction in mice squirms of 22.49